Autonomous systems: A bibliometric and patent analysis - Jan Youtie; Alan L. Porter; Philip Shapira; Seokkyun Woo; Yayun Huang (Expertenkommission Forschung und Innovation (EFI), 2017)
This report examines Germany's research and patent position in four autonomous systems: smart homes, smart factories, autonomous vehicles (non-hostile environments), and autonomous vehicles in hostile environments. Bibliometric analysis of scholarly papers indexed in the Web of Science and patent analysis of documents in Patstat and Derwent Innovation Index (representing patents from more than 40 patent authorities worldwide) are conducted for all records published in the 2002 to 2017 (May) time period. [...]
Keywords: 330